Timing of parenteral nutrition initiation in critically ill children: a randomized clinical trial - Nagwan Y. Saleh; Hesham M. Aboelghar; Nehad B. Abdelaty; Mohamed I. Garib; Asmaa A. Mahmoud (The Korean Pediatric Society, 2023)
Background The optimal timing of parenteral nutrition (PN) initiation in critically ill children remains controversial. Purpose To identify the optimal timing of PN initiation in critically ill children. Methods This randomized clinical trial was conducted in the pediatric intensive care unit (PICU) of Menoufia University Hospital. A total of 140 patients were randomized to receive early or late PN. The early PN group consisted of 71 well-nourished and malnourished patients who received PN on the first day of PICU admission. Malnourished (42%) and well-nourished children randomized to the late PN group (42%) started PN on the fourth versus seventh day after admission, respectively. Mechanical ventilation (MV) was the primary outcome, while PICU length of stay and mortality were secondary outcomes. Results Patients who received early PN started enteral feeding significantly earlier (median, 6 days; interquartile range, 2-20 days) than those not provided early PN (median, 12 days; interquartile range, 3-30 days; P<0.001) and had a significantly lower risk of feeding intolerance (5.6% vs.18.8%, P=0.035). The median time required to obtain full calories enterally was shorter in the early versus late PN group (P=0.004). Furthermore, patients in the early versus late PN group had a significantly shorter median PICU stay (P<0.001) and were less likely to require MV (P=0.018). Conclusion Patients who received early PN had a lower MV need and duration than those who received later PN and had more favorable clinical outcomes in terms of morbidity.